1998
DOI: 10.2527/1998.76102657x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptus, progesterone, and breed effects on uterine protein secretion in swine.

Abstract: This experiment consisted of the following treatment-breed groups: 1) White crossbred gilts, 2) White crossbred gilts treated with progesterone (200 mg/d in corn oil given on d 2 and 3 after estrus), and 3) Chinese Meishan gilts. Pregnant and nonpregnant gilts (n=3 to 6) from each treatment-breed combination were assigned to be slaughtered on d 10, 11, 12, 13, and 15. At slaughter each uterine horn was flushed with 20 mL of minimal essential medium. Uterine flushings were assayed for total protein, acid phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
2
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 37 publications
4
41
2
2
Order By: Relevance
“…However, our present data estimating P4 in the caval vein and those reported from peripheral blood collection [13,14] do not confirm such a P4 increase. It has also been suggested that the P4 level on Days 2 and 3 of pregnancy influences conceptus development [29]. Our data did not find a relation between the P4 concentration on Day 3 and pregnancy outcome.…”
Section: Gnrh Agonist Effects In Pregnant Giltscontrasting
confidence: 51%
“…However, our present data estimating P4 in the caval vein and those reported from peripheral blood collection [13,14] do not confirm such a P4 increase. It has also been suggested that the P4 level on Days 2 and 3 of pregnancy influences conceptus development [29]. Our data did not find a relation between the P4 concentration on Day 3 and pregnancy outcome.…”
Section: Gnrh Agonist Effects In Pregnant Giltscontrasting
confidence: 51%
“…As progesterone is involved in secretory functions in the uterus (Adams et al 1981, Roberts et al 1987, Vallet et al 1998, differences in PR immunopresence could therefore be expected. Our results support this concept by showing PR differences between surface and glandular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…A stimulatory effect by progesterone on uterine protein secretion has been shown in pigs in several studies (Adams et al 1981, Roberts et al 1987, Vallet et al 1998. During pregnancy progesterone has an important role in preparations for uterine reception of the early embryos and for the maintenance of pregnancy.…”
Section: Introductionmentioning
confidence: 94%
“…Meishan pigs are prolific breeders, averaging three to five more pigs per litter than the European breeds, even though their ovulation rates are similar (Ford and Youngs 1993;Haley et al 1995;Vallet et al 1998). Gene expression in the endometrium of different breeds may relate to reproduction traits.…”
Section: Discussionmentioning
confidence: 99%